USTADZ SELEBRITI ABDULLAH GYMNASTIAR DALAM BUDAYA POPULER (PERSPEKTIF HIPERSEMIOTIKA YASRAF AMIR PILIANG) - Maskur, Maskur; Noor, Irfan (Faculty of Ushuluddin and Humanities, 2014)
The development of popular culture, in particular the development of information technology develops so fast as television, mobile phones and internet network as a part of the development of information technology, ultimately, it has an impact on the creation of a new reality called hyper reality. Media in this case were able to reconstruct a new reality through technological sophistication. The construction of this media also comes into the religious sphere. This can be seen in the figure of an Abdullah Gymanstiar (Aa Gym). Through the media of information, Aa Gym is not only known as an Islamic priest who offers a depth of spirituality but he is also as a celebrity through the image formed. This paper aims to identify and describe the phenomenon of celebrity ustadz, Abdullah Gymnastiar in popular culture, by using hyper semiotics approach Yasraf Amir Piliang.